Sardinization of the event in the novel Beit al-Sudan al-Muhammad Hayawi - Qaddouri, Walaa Fakhri (Al-Adab Journal, 2021)
The author (Muhammad Hayawi) Eidalia chose to research the artistic techniques of his novel to a large extent coherent, so this research studied the relevance of the event in the novel (The House of Sudan) with greed and descriptive analysis to reveal the artistic and aesthetic dimensions of the event and to derive the implications that resulted from it. The novel revealed the ordeal of existence through the station of the body and the identity with an intellectual and secular (human) vision. The research was based on localization and three axes, and the first axis was devoted to the study of (Hatabah identity). While the second axis includes the study of dreams in the narrator). As for the third axis, it came to a study of the narrative employment of cinematic technologies). This research concluded with a number of critical results that make narration of the event in the novel.